2021
DOI: 10.1515/ntrev-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of microcrystalline and nanocrystalline cellulose from Ananas comosus L. leaves: Cytocompatibility and molecular docking studies

Abstract: The present study focused on the preparation of microcrystalline cellulose (MCC) and nanocrystalline cellulose (NCC) from pineapple (Ananas comosus L.) leaves using chemical treatments followed by acid hydrolysis. Pineapple leaves could be used in medical applications such as drug delivery carriers. Advanced spectroscopy techniques such as Fourier-transform infrared (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) were used to analyze the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…The particle size of BNS-MCC ranges from about 100-500 microns, with about 97% of the particle population less than 154 µm. Particle size depends upon the extent of degradation of cellulose molecule [30]. Finer particle size BNS-MCC promotes tablet (compact) strength as confirmed by the researchers.…”
Section: Particle Size Distributionsupporting
confidence: 52%
“…The particle size of BNS-MCC ranges from about 100-500 microns, with about 97% of the particle population less than 154 µm. Particle size depends upon the extent of degradation of cellulose molecule [30]. Finer particle size BNS-MCC promotes tablet (compact) strength as confirmed by the researchers.…”
Section: Particle Size Distributionsupporting
confidence: 52%
“…The biomass generated in pineapple production has been used mainly to extract cellulose nanocrystals. The CNC obtained are by acid hydrolysis and it has been reported that they are extracted from different parts of the pineapple plant such as the crown [22,23], the stem [3], the peel [24] and the leaves [25,26]. Due to the cellulosic availability in pineapple plant, it is important to explore the possibility of producing CNF from this raw material.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly,Sainorudin et al (2021) reported a decrease in the band intensity of nanocrystalline cellulose between 1637.56 and 1639.49 cm −1 , attributed to the carbonyl group stretching vibration of lignin ferulic and p-coumaric acid carboxylic group, or hemicellulose acetyl and uronic ester groups confirming that acid hydrolysis removes these extraneous components. In another study, de Souza et al (2019) prepared CNSs from industrial paper wastes using acid hydrolysis and pretreatments with alkali and acid.…”
mentioning
confidence: 83%
“…The calculated crystallinity for CNSs was 48.5% and 31.5% for first and second methods, respectively (Manzato et al, 2017). cellulose structure and strong diffraction peaks at 22°with a CI of 76.38% was reported by Sainorudin et al (2021). The CI increased due to the organized molecular structure of small particles and the fiber's strength and stiffness.…”
Section: Wide-angle/small Angle X-ray Diffractionmentioning
confidence: 95%